Demographic assessment of the information literacy competency of freshmen UPCAT passers at the University of the Philippines Los Banos - Ingua, Mary Ann M.; Gonzales, Grace Marie B.; Mallari, Florenda D. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2007)
The study was conducted to assess the information literacy competency of the Freshmen UPCAT passers, in order to examine the relationship between the demographic data and information literacy based on the Association of College & Research Libraries (ACRL) information literacy competency standards for higher education.
The study focused only on Freshmen UPCAT passers enrolled during the first semester, AY-2005-2006. A questionnaire, composed of 16 questions to determine the demographic data of the respondents and 86 multiple choice items based on the ACRL Information Literacy Competency Standards for Higher Education was used to collect the data. Analysis of variance (ANOVA), Duncan's multiple range test (DMRT), frequency and percentage of scores, and chi-square test of independence were used to test the hypotheses and to determine the relationship between the dependent and independent variables.
Comparing the results of information literacy competency examination of the respondents based on the five (5) information literacy competency standards, it can be concluded that there are significant differences established among the ACRL Information Literacy Competency Standards for higher education in terms of information literacy competency of the respondents.
From the result, the respondents excelled best in determining the nature and extent of the needed information. They can evaluate the information and its sources critically and incorporate selected information into their research. As an individual or as a member of a group, they can use the information effectively in accomplishing a specific purpose.
On the other hand, respondents are weak or poor in terms of familiarity with the type of information contained in a particular system or database. They are poor in selecting the appropriate retrieval system for a research topic and in investigating the scope, content, organization, and "help" tool. They have difficulties in constructing and implementing effectively-designed search strategies and in retrieving the information online or in person. They are also weak in terms of recording and managing the information sources, particularly in giving citations and recognition to the author and publisher of the work. They are also weak in understanding the economic, legal and social issues surrounding the use and access of the information.
The gender, citizenship, socio-economic status, honors received, library orientation/workshop, or region/province, are not reliable predictors of the information literacy competency because of the uneven distribution of respondents from each demographic data.
UP Administered and Public Science/Special high schools are the types of high schools in the region that can be considered as one of the bests in terms of information literacy competency, although the "statistically significant definition" was not large enough to be truly impressive. Science oriented curriculum got the highest information literacy competency followed by General Secondary and the Accelerated Christian Education Curriculum. The lowest information literacy competency came from Vocational-Technical Curriculum. Those who are living in dormitories that are near or inside the campus got high information literacy competency compared with those living in their own homes.
Use of internet and reference materials plays a significant role in the respondents' information literacy competency. Respondents who used the internet got higher information literacy competency.
Respondents who underwent training got the highest information literacy competency compared with respondents who did not receive any training on information retrieval.
The poor performance of respondents in ACRL ILC standard 2 and standard 5, shows that respondents really need to be given the attention to participate in information literacy programs in the campus to ensure that they will be aware of these different information sources and be particular with how these resources are useful in their researches.
It is recommended that UPLB librarians should coordinate with faculty members regarding students' assignments and orient them with the Library's resources, as this may lead to and/or give importance to the use of information sources particularly the online databases their contents and organization, searching strategies, as well as the legal and ethical issues in using this information. Information literacy program, either in a group or individual sessions can be implemented to support the need of the students for information literacy. Through this study, educators and the general public will be aware that information literacy is a fundamental competency skill for lifelong learning. Moreover, they will be supportive enough to incorporate information literacy into the education curriculum and work place and to disseminate knowledge of information literacy through publications and colleagues and most importantly to provide universities and colleges with an information literacy-developing model and assessment tools or systems. Library professional organizations like the Philippine Librarians Association Inc. (PLAI), Philippine Association of Academic Research Libraries (PAARL), Philippine Association of School Librarians (PASL) can spearhead in the promotion of information literacy in the country as this topic can be included in seminars and conferences.
Vita.
Thesis (Master of Library and Information Science)--University of the Philippines Diliman
Keywords: University of the Philippines, Los Banos -- College freshmen; Information Literacy -- Evaluation. -- Philippines -- Los Banos, Laguna